Figurative Language Used In The Cold Play Album - Amri, Ikhvan Assafa (2012)
This research is aimed at examining the kinds of figurative language and analyzing the meaning of those figurative languages in particular contextual meaning. The research type conducted by the writer is descriptive qualitative research. The data source of this research is taken from the manuscript of song lyrics of Coldplay Album. The writer employs documentation as the method of collecting data with the steps: collecting the data, reading, rewriting, and classifying the data. In analyzing the data, the writer examines the kinds of figurative language found in Coldplay Album by referring to the theory from Larson in his book "Meaning-Based Translation" and Saeed in his book "Semantics". Describe the meaning of figurative language sentence that found in Coldplay Album by referring to contextual meaning. Based on the result of the data analysis, the writer found the kinds of figurative language in Coldplay album, there are six kinds of figurative language from eleven data that been used in Coldplay Viva La Vida and Death All His Friend album. They are Metaphor (1 data, 9%), Personification (1 data, 9%), Apostrophe (2 data, 19%), Metonymy (3 data, 27%), Hyperbole (3 data, 27%), and symbol (1 data, 9%), and there are seven kinds of figurative language from thirty two data that have been used in Coldplay Mylo Xyloto album. They are Simile (5 data, 16%), Metaphor (10 data, 31%), Personification (1 data, 3%), Metonymy (6 data, 19%), Synecdoche (1 data, 3%), Hyperbole (7 data, 22%), and Symbol (2 data, 6%). The meaning that found in this paper is about the struggle of France people in the France Revolution, expression freedom in New York Old graffiti and White Rose Movement.